Innovative Design of Speed Control Bump Based on SolidWorks - LI, Shu'jia; ZHANG, Haitian; WANG, jie (IJRDO - Journal of Mechanical And Civil Engineering, 2019)
Human society consumes a lot of energy in the long process of development. Nowadays, as the foundation of economic and social development, energy has become a top priority for social development. It has become an urgent research focus how to collect, utilize and save energy. Through the analysis and research of the road speed reducer, a power generation device based on deceleration zone was designed and developed by using SolidWorks. The device utilizes the contact process of the car and the speed control bump to collect energy and store it in the form of electricity, thereby achieving the purpose of energy recycling.